2014
DOI: 10.4315/0362-028x.jfp-13-056
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness of Electronic Reporting and Acceptability of Public Health Follow-Up of Routine Nonparatyphoidal and Nontyphoidal Salmonella Infections, London and South East England, 2010 to 2011

Abstract: Nonparatyphoidal and nontyphoidal Salmonella (NTS) infections are major causes of food poisoning in England. Diagnostic laboratories and clinicians have a statutory responsibility to report NTS infection cases to the Health Protection Agency via various means, with electronic reporting encouraged as the universal method. The Health Protection Agency (Public Health England since 1 April 2013) refers cases to environmental health departments for follow-up. Timeliness of reporting and adequacy of NTS infection ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…However, none of these studies fulfilled the predefined timeframe, and only 2 the standardized timeframe [ 10 , 44 ]. In 3 studies, conventional reporting method was as fast as, or faster than electronic systems [ 26 , 32 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, none of these studies fulfilled the predefined timeframe, and only 2 the standardized timeframe [ 10 , 44 ]. In 3 studies, conventional reporting method was as fast as, or faster than electronic systems [ 26 , 32 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…This attribute was included in 18 studies [13,15,16,21,27,31,34,[40][41][42][43][44][45][46][47][54][55][56], all using the same method (retrospective analysis of routinely collected data) but different reference periods to measure timeliness. These included the interval between the onset of symptoms and the notification to health authorities [40,43]; specimen collection to case reporting [27,42,54]; isolation at the primary laboratory to reporting to the surveillance body [47]; onset of symptoms to completion of case investigation [44]; reporting within one week of starting treatment [31]; starting treatment to notification [21]; notification within one or two incubation periods [40]; reporting delays regularly more than three months [13].…”
Section: Timelinessmentioning
confidence: 99%
“…With the exception of one [16], all evaluations reported that timeliness of reporting could be improved, and some recommended that future research should explore the bottlenecks in the reporting process [41,42]. Suggestions made for improving the timeliness of reporting included transmitting laboratory reports electronically [56], reducing the laboratory electronic reporting period [55], and sending a sample of isolates to the national reference laboratory while the isolate is being analysed at the primary laboratory to reduce the delays incurred by waiting for the results of partial analysis [47].…”
Section: Timelinessmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases of food poisoning involve a short incubation period. Thus, timeliness of reporting is a crucial factor that influences the implementation of effective public health interventions [8]. The key strength of an outbreak investigation is determined by how rapid the public health acts and initiates coordination across multiple organizations [9].…”
Section: Introductionmentioning
confidence: 99%